2023
DOI: 10.3389/fphar.2023.1188202
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of baicalin in lung diseases

Abstract: The flavonoids baicalin and baicalein were discovered in the root of Scutellaria baicalensis Georgi and are primarily used in traditional Chinese medicine, herbal supplements and healthcare. Recently, accumulated investigations have demonstrated the therapeutic benefits of baicalin in treating various lung diseases due to its antioxidant, anti-inflammatory, immunomodulatory, antiapoptotic, anticancer, and antiviral effects. In this review, the PubMed database and ClinicalTrials website were searched with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 121 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…It is known that circRNAs form a covalently closed loop and regulate gene expression, leading to governing cellular processes. Accumulating evidence has suggested that circRNAs play a critical role in osteoarthritis initiation and progression (Wu and Zou, 2021;Wang et al, 2023;Li and Lu, 2023;Xue et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that circRNAs form a covalently closed loop and regulate gene expression, leading to governing cellular processes. Accumulating evidence has suggested that circRNAs play a critical role in osteoarthritis initiation and progression (Wu and Zou, 2021;Wang et al, 2023;Li and Lu, 2023;Xue et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA SNHG1 also alleviated the expression of MMPs, aggrecan, collagen, and ADAMTs in chondrocytes (Lei et al, 2019). Wang et al reported that lncRNA SNHG1 reduced cell apoptosis and inflammation via influencing the miR-195/IKK-α axis in chondrocyte (Wang et al, 2023). LncRNA SNHG5 increased proliferation of chondrocyte via targeting miR-26a/SOX2 axis in OA (Shen et al, 2018).…”
Section: Lncrna Snhgsmentioning
confidence: 97%
See 2 more Smart Citations
“…Through this expedient, the easy break of the DA disulfide bonds may be obtained in the TME, where GSH is present at high concentrations, thereby leading to the specific release of the loaded bioactive compounds. Finally, the co-delivered baicalein seems a highly appropriate choice, this bioactive natural compound produced by the plant Scutellaria baicalensis Georgi has been demonstrated to exert multiple beneficial effects in treating a variety of lung diseases, including lung cancer [ 141 ].…”
Section: Newly Developed Ha-based Nanocarrier Systems Loading Phecs A...mentioning
confidence: 99%